Vitamin D serum levels and the risk of digital ulcers in systemic sclerosis: A longitudinal study. (2nd April 2019) - Caimmi, Cristian; Bertoldo, Eugenia; Pozza, Alice; Caramaschi, Paola; Orsolini, Giovanni; Gatti, Davide; Rossini, Maurizio; Viapiana, Ombretta
Abstract: Aim: Low levels of vitamin D (25OHD) have been found to associated with digital ulcers (DUs) in systemic sclerosis (SSc), although only cross‐sectional studies have been performed. We aimed to investigate if variations in vitamin D serum levels over time affect DU in SSc. Methods: This is a retrospective study on 65 patients. 25OHD was measured in 2011 and 2016 and its variations correlated with DU. Results: The mean age of our cohort was 58 (SD 12) years with a mean disease duration of 9.5 (5.3) years. Most of our patients had a limited SSc (69.2%). At baseline 50.8% and 41.5% after 5 years had 25OHD <30 ng/mL. Patients receiving supplementation (8750 IU/wk) at baseline numbered 39 (60.0%) and 45 (69.2%) at the end of follow up. Nevertheless, 31 (47.7%) had a decrease of 25OHD in 5 years. In univariate analysis, patients with incident DU had a decrease in 25OHD as compared to patients with no incident DU (−17.4 [37.0] vs 13.0 [89.5], P = 0.018). No differences in 25OHD variations were found for other disease characteristics. In multivariate analysis correcting for previous DU and modified Rodnan Skin Score at baseline, patients with a decrease in 25OHD had an increased risk of developing DU (odds ratio 16.6; 95% CI 1.7‐164.5, P = 0.017). Conclusions: A decrease in 25OHD is associated with the risk of developing DUs. In addition, vitamin D supplementation with the doses currently recommended may be insufficient in SSc. Further studies in wider cohorts are needed to confirm these results.